New insights into the burden and costs of multiple sclerosis in Europe - Kobelt, Gisela; Thompson, Alan; Berg, Jenny; Gannedahl, Mia; Eriksson, Jennifer (Multiple sclerosis, 2017)
The current focus in multiple sclerosis (MS) is on early diagnosis and drug intervention, with a view to modifying disease progression. Consequently, healthcare costs have shifted from inpatient care and rehabilitation to outpatient care. This European burden of illness study provides data that can be combined with other evidence to assess whether management approaches provide value to society. A cross-sectional study was conducted in 16 countries. Patients reported on their disease, health-related quality of life (HRQoL) and resource consumption. Descriptive analyses were performed by disease severity. Costs are reported from a societal perspective in 2015€ PPP (adjusted for purchasing power parity). The 16,808 participants had a mean age of 51.5 years, and 52% had relapsing-remitting multiple sclerosis (RRMS). Work capacity declined from 82% to 8%, and utility declined from normal population values to less than zero with advancing disease. Mean costs were 22,800€ PPP in mild, 37,100€ PPP in moderate and 57,500€ PPP in severe disease; healthcare accounted for 68%, 47% and 26%, respectively. Fatigue and cognitive difficulties were reported by 95% and 71% of participants, respectively; both had a significant independent effect on utility. Costs and utility were highly correlated with disease severity, but resource consumption was heavily influenced by healthcare systems organisation and availability of services.